Oleyl Conjugated Histidine-Arginine Cell-Penetrating Peptides as Promising Agents for siRNA Delivery - Muhammad Imran Sajid; Dindyal Mandal; Naglaa Salem El-Sayed; Sandeep Lohan; Jonathan Moreno; Rakesh Kumar Tiwari (MDPI AG, 2022)
Recent approvals of siRNA-based products motivated the scientific community to explore siRNA as a treatment option for several intractable ailments, especially cancer. The success of approved siRNA therapy requires a suitable and safer drug delivery agent. Herein, we report a series of oleyl conjugated histidine-arginine peptides as a promising nonviral siRNA delivery tool. The conjugated peptides were found to bind with the siRNA at N/P ratio ≥ 2 and demonstrated complete protection for the siRNA from early enzymatic degradation at N/P ratio ≥ 20. Oleyl-conjugated peptide -siRNA complexes were found to be noncytotoxic in breast cancer cells (MCF-7 and MDA-MB-231) and normal breast epithelial cells (MCF 10A) at N/P ratio of ~40. The oleyl-R3-(HR)4 and oleyl-R4-(HR)4 showed ~80-fold increased cellular uptake in MDA-MB-231 cells at N/P 40. Moreover, the conjugated peptides-siRNA complexes form nanocomplexes (~115 nm in size) and have an appropriate surface charge to interact with the cell membrane and cause cellular internalization. Furthermore, this study provides a proof-of-concept that oleyl-R5-(HR)4 can efficiently silence STAT-3 gene (~80% inhibition) in MDA-MB-231 cells with similar effectiveness to Lipofectamine. Further exploration of this approach holds a great promise in discovering a successful in vivo siRNA delivery agent with a favorable pharmacokinetic profile.